International legal protection of the right to the education of migrant children - Tlepina, Sh.V.; Akshalova, R.D.; Ramazan, A.E. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
The education of children from migrant families is a pressing issue, with approximately 36 million school-age children and adolescents among international migrants, a number that continues to rise. Their education is an important long–term strategic priority and an investment in the future of the whole world. The article examines the problems of the education of migrant children, considers the recommendations for different countries in the field of organizing access of children to preschool, primary and secondary education, the creation of a favorable environment. Special attention is given to issues related to access to education, adaptation in the educational environment, and overcoming language barriers. The choice of a particular integration model depends on the immigration history of each country. Some integration models contribute to the formation of a multicultural society, while others aim at the complete assimilation of migrants. The selected models of realization of the right to the education of migrant children are reflected in the education system and determine how it will respond to the challenges associated with an increase in the number of children from migrant families in educational institutions. The study results highlight the necessity of creating efficient policies to safeguard the educational rights of migrant children.